2021
DOI: 10.1155/2021/6659146
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effects of Erbium Chromium Laser along with/without Silver Nanoparticles in Root Canals Infected by Enterococcus faecalis

Abstract: This study investigates the antibacterial effects of erbium chromium laser at 2780 nm, silver nanoparticles, and erbium chromium along with silver nanoparticles on Enterococcus faecalis in comparison with sodium hypochlorite. In the present study, 90 extracted human single-rooted teeth were selected and standardized to a length of 15 mm. The canals were prepared by V-taper Gold rotary files and then incubated with E. faecalis for 21 days. The samples were divided into four experimental groups including hypochl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Some studies concluded that using a diode laser merely is not effective enough in disinfecting root canals, and it must be used as an adjunct therapy after or during NaOCl irrigation. 26,33,34,36 In contrast, some other studies indicated that the diode laser is effective and acceptable when used solely. 12,19,20 Moreover, when Er, Cr: YSGG is utilized solely, it does not eradicate root canal bacteria effectively; however, using this laser with LAI technique with silver nanoparticles, NaOCl or saline showed acceptable outcomes in disinfecting the root canal system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies concluded that using a diode laser merely is not effective enough in disinfecting root canals, and it must be used as an adjunct therapy after or during NaOCl irrigation. 26,33,34,36 In contrast, some other studies indicated that the diode laser is effective and acceptable when used solely. 12,19,20 Moreover, when Er, Cr: YSGG is utilized solely, it does not eradicate root canal bacteria effectively; however, using this laser with LAI technique with silver nanoparticles, NaOCl or saline showed acceptable outcomes in disinfecting the root canal system.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Er, Cr: YSGG When the Er, Cr: YSGG laser is used solely, it could not effectively destroy bacteria, and its bacterial reduction rate is almost 50%. 29,33,34 However, antibacterial outcomes comparable to gold standard NaOCl irrigation have been reported by studies in which the Er, Cr: YSGG laser was used with the LAI technique with silver nanoparticles, 33 NaOCl, 29,30,[34][35][36][37][38][39][40] and saline. [36][37][38] It has been mentioned in the literature that the disinfection potential of the LAI technique with Er, Cr: YSGG significantly improved by increasing irradiation time.…”
Section: Diodementioning
confidence: 99%